The Role of the Khilafat Movement in the Relationship Between the Ottoman Empire and the Muslims of India - Zekai Kardaş (Şarkiyat Mecmuası)
With the Ottoman Empire taking over the Caliphate at the beginning of 16th century, an intangible bond started to appear between the people of the Indian subcontinent, the majority of whom were Muslims, and the Ottoman Empire, and the relationships between them begun to increase gradually. After the Britain’s dominance over India in particular, the Muslims of the subcontinent considered the Caliph as their Maecenas [generous patron], protector of the rights they’d gained by being Muslim, and the maintainer of their freedom to pray as Muslims. They kept track of the incidents would soon happen to the Ottomans in the Balkan Wars and tried to find every possible way to help and support the Turks. Britain’s entry into World War I against the Ottoman Empire caused outrage among the Indian Muslims. The Indian Khilafat [Caliphate] Movement was initiated by Indian Muslims to suppress the British government and protect the Ottoman Caliphate. The Hijrat Movement emerged as a result of the Indian Caliphate Movement. The leading religious and political leaders of India put forward the ideas that India, which was ruled by the British, was no longer a place where Muslims could fulfill their religious obligations and that they should migrate to other places.